СОЦИАЛЬНО-ФИЛОСОФСКОЕ ОСМЫСЛЕНИЕ ФЕНОМЕНА РЕКЛАМЫ - Васильева, Л. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Автор досліджує онтологічний та аксіологічний зріз феномена реклами як визначальних у соціально-філософському аспекті даного соціокультурного простору. Автор доводить, що як одне з інноваційнихявищ сучасної комунікативної дійсності, реклама транслює свою історію через так звані «інформаційніреволюції», які мали місце в окремі визначені економічно-культурні періоди суспільства. Саме становленняфеномену реклами як діяльності, творчості і продукту таїть у собі різноманітні тлумачення її генезису,змісту і функцій.Васильева Л. СОЦИАЛЬНО-ФИЛОСОФСКОЕ ОСМЫСЛЕНИЕ ФЕНОМЕНА РЕКЛАМЫ. Авторисследует онтологический и аксиологический срез феномена рекламы как определяющих в социально-философском аспекте данного социокультурного пространства. Автор доказывает, что как одно изинновационных явлений современной коммуникативной действительности, реклама транслирует своюисторию через так называемые «информационные революции», которые имели место в определенныеэкономико-культурные периоды общества. Именно становление феномена рекламы как деятельности,творчества и продукта таит в себе различные толкования ее генезиса, содержания и функций.Ключевые слова: феномен рекламы, коммуникативная действительность, «информационныереволюции».L. Vasiljeva. THE SOCIAL-PHILOSOPHICAL PERCEPTION OF PHENOMENON OF ADVERTISEMENT.The author explores the ontological and axiological cutoff of the phenomenon of advertisement, as a definer in thesocio-philosophical aspects of the social and cultural phenomenon. The author argues that as one of the innovativephenomenon of modern communicative reality, advertisement broadcasts its history through the so-called"information revolutions" that occurred in certain specified periods of economic-cultural society. In the article theauthor stresses that the development of a business like advertisement, creativity and product carries a differentinterpretation of its genesis, contents and functions.Key words: phenomenon of advertisement, communicative reality, "information revolutions".